2022
DOI: 10.1186/s13019-022-01930-7
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid convergent ablation versus endocardial catheter ablation for atrial fibrillation: a systematic review and meta-analysis of randomised control trials and propensity matched studies

Abstract: Introduction Atrial fibrillation (AF) is the most common arrhythmia. Hybrid convergent ablation (HCA) is an emerging procedure for treating longstanding AF with promising results. HCA consists of a subxiphoid, surgical ablation followed by completion endocardial ablation. This meta-analysis of randomized control trials (RCT’s) and propensity score-matched studies aims to examine the efficacy and safety of HCA compared to endocardial catheter ablation (ECA) alone on patients with AF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…It is well-known that the inclusion of unmatched retrospective data into meta-analyses may jeopardize the results. Therefore, a recent meta-analysis analyzed the rhythm outcomes of hybrid ablation vs. CA in only randomized-controlled and propensity-matched studies ( 49 ). Authors confirmed how the hybrid group had significantly higher rates of freedom from AF with [odds ratio (OR) =2.78; 95% confidence interval (CI): 1.82–4.24; P<0.001] or without AAD (OR =2.75; 95% CI: 1.63–4.65; P<0.001) than the CA group.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that the inclusion of unmatched retrospective data into meta-analyses may jeopardize the results. Therefore, a recent meta-analysis analyzed the rhythm outcomes of hybrid ablation vs. CA in only randomized-controlled and propensity-matched studies ( 49 ). Authors confirmed how the hybrid group had significantly higher rates of freedom from AF with [odds ratio (OR) =2.78; 95% confidence interval (CI): 1.82–4.24; P<0.001] or without AAD (OR =2.75; 95% CI: 1.63–4.65; P<0.001) than the CA group.…”
Section: Discussionmentioning
confidence: 99%
“…29 The benefit of hybrid ablation over catheter ablation alone is further documented by several meta-analyses. [30][31][32] Given these data, we should anticipate increased uptake among surgeons in the coming years.…”
Section: Tale Of Two Trials In Support Of Hybrid Ablation For Persist...mentioning
confidence: 99%
“…62 A meta-analysis showed that hybrid ablation with surgical epicardial ablation along with LAAO followed by endocardial catheter ablation achieved more days free from atrial tachyarrhythmias at final follow-up than endocardial catheter ablation alone. 63 Since DCD was one of the dominating topics of 2023, the authors also recap the American Society of Transplant Surgeons Recommendations on Best Practices in Donation after Circulatory Death Organ Procurement. 64 Last, as morbidity and survival after cardiac surgery continue to improve, the review emphasized the importance of cognitive changes after surgery.…”
Section: Cardiothoracic Surgerymentioning
confidence: 99%
“…62 A meta-analysis showed that hybrid ablation with surgical epicardial ablation along with LAAO followed by endocardial catheter ablation achieved more days free from atrial tachyarrhythmias at final follow-up than endocardial catheter ablation alone. 63…”
Section: Cardiothoracic Surgerymentioning
confidence: 99%